State of resistance : what California's dizzying descent and remarkable resurgence mean for America's future - Pastor, Manuel, 1956- (The New Press, 2018)
"Once upon a time, any mention of California triggered unpleasant reminders of Ronald Reagan and right-wing tax revolts, ballot propositions targeting undocumented immigrants, and racist policing that sparked two of the nation's most devastating riots. In fact, California confronted many of the challenges the rest of the country faces now--decades before the rest of us. Today, California is leading the way on addressing climate change, low-wage work, immigrant integration, overincarceration, and more. As white residents became a minority and job loss drove economic uncertainty, California had its own Trump moment twenty-five years ago but has become increasingly blue over each of the last seven presidential elections. How did the Golden State manage to emerge from its unsavory past to become a bellwether for the rest of the country?"--